Effects of IPO timing on the underpricing of shares of companies listed on the Nairobi Securities Exchange (NSE), Kenya - Mutai , Joseph (African Journal of Education,Science and Technology (AJEST), 2019)
One of the most intriguing aspects associated with (initial public offerings (IPOs) is the apparent abnormal increase in share price on the first day of trading. Although the phenomenon has been subject to a plethora of explanations, none of them has been sufficiently acceptable. Few studies have looked at the possible explanations for the short run underpricing of IPOs of listed companies in Kenya. The objective of this study was to investigate the effect of IPO timing on underpricing of shares of companies listed on the NSE. An explanatory survey design was adopted for the study, with IPO timing (the date of the IPO offer) as the explanatory variable while first-day return was the endogenous variable. The target population of the study was 12 companies that had sold shares to the public between January 1996 and December 2013 and 54 other companies on the Stock Exchange, which were used to compute benchmarks (NSE-20 share index), against which the companies that had issued IPOs in the study were compared. The entire population (census) of the companies was used in the study, as the target population was small. The study analysed company data (prospectuses and annual statements) and the stock share price on the first day of trading after IPO from the NSE. The study found an average under-pricing of 55.36% and a median under-pricing of 24.71%, with all companies except one, having had its offer price under-priced. Short run underpricing was always found, regardless of the type of industry, the nature of ownership of the firm, age of the company or the size of the IPO offer. However, the study found that the more an IPO was oversubscribed, the more the abnormal return that ensued (r=0.59, p=0.046). Regression analyses revealed that the prevailing market sentiment is a significant predictor of abnormal initial return, with more significant underpricing occurring during bull markets compared with bear markets (β= .603, t=2.393, p=0.038). The study thus found evidence for the importance of “investor sentiment” in explaining short run underpricing. The study recommends that investors should rationally analyse each company performance and history before investing in the IPO, rather than joining the ‘band wagon’ of investment as oversubscribed issues experience more significant underpricing